2012
DOI: 10.5402/2012/532168
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Nanocrystalline Ni0.5Zn0.5Fe2O4 Thin Film from Aqueous Sulfate Bath

Abstract: Nanocrystalline nickel-zinc ferrites Ni 0.5 Zn 0.5 Fe 2 O 4 thin films have been synthesized via the electrodeposition-anodization from the aqueous sulfate bath. The electrodeposited (Ni-Zn)Fe 2 alloy was anodized in aqueous 1 M KOH solution to form the corresponding hydroxides which annealed at different temperatures ranging from 800 to 1000• C for various periods from 1 to 4 h, to get the required ferrite. SEM micrograph of the formed ferrite particles, annealed at 1000• C for 4 h appeared as the octahedral-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…It was observed that with increasing temperature, the lattice parameter, the network microdeformation and the cell volume decrease, and the material density increase, a result that agrees with Saba et al [32] Zhang et al [43] and Mouallem-Bahout et al [31], who calcined Ni-Zn ferrite at 800°C for 240 min, 900°C for 120 min, and 650°C for 900 min, respectively. Figure 2 shows the thermal analysis of Ni-Zn ferrite precursor powders.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…It was observed that with increasing temperature, the lattice parameter, the network microdeformation and the cell volume decrease, and the material density increase, a result that agrees with Saba et al [32] Zhang et al [43] and Mouallem-Bahout et al [31], who calcined Ni-Zn ferrite at 800°C for 240 min, 900°C for 120 min, and 650°C for 900 min, respectively. Figure 2 shows the thermal analysis of Ni-Zn ferrite precursor powders.…”
Section: Resultssupporting
confidence: 84%
“…The reaction of Zn with oxygen and the relationship between the partial Zn and O 2 pressures can be understood by the following expression (Eq. 4) [39]: [32,42,43]. Table 2 shows a tendency of increasing the average crystallite size with increasing calcination temperature.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Cheaper electrochemical deposition technique has also been demonstrated to be able to fabricate textured barium ferrite films. In comparison, the electrochemical deposition technique provides not only the possibility of using low synthesis temperature but also low cost of starting materials and a high purity of the product yield (Saba et al 2011;Gomes et al 2004;Roy and Verma 2006;Nuli and Qin 2005;Sartale et al 2003Sartale et al , 2004Saba et al 2012). Until now, the electrochemical performance of ferrite thin films at different pH values is not mentioned in detail in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The transients have been analyzed by comparing the chronoamperometric curves to the dimensionless theoretical curves for the diffusioncontrolled nucleation and growth of crystals in three dimensions (3D) proposed by Saba et al [20] and Kim et al [29] The expressions for the instantaneous and progressive nucleation are given by the following equations, respectively [28,30] Where imax and tmax are the maximum current density observed at the maximum time tmax. …”
Section: Influence Of Bath Agitationmentioning
confidence: 99%